Interactions between care-giving and paid work hours among European midlife women, 1994 to 1996 - Christa Katharina Spieß; A. Ulrike Schneider (Ageing & Society, 2003)
This paper uses data from the European Community Household Panel surveys of 1994 and 1996 to study the association between changes in care-giving and changes in weekly work hours. Our sample comprises women aged 45-59 years who participated in the labour force in at least one of the two years studied. Controlling for country variation, we find significant relationships between starting or increasing informal care-giving and changes in weekly work hours. No such association is found however among women terminating a care-giving commitment or reducing their care hours. Starting care-giving significantly reduces work hours for women in northern European countries (except Ireland). By contrast, women in southern Europe and Ireland respond to an increase in care-giving hours by a smaller increase or a higher decrease in work hours than non care-givers. In summary, our results show that the impact of care-giving on adjustments of weekly work hours is asymmetrical and that it differs in southern and northern Europe.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich. - This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively
Keywords: 330; Weibliche Arbeitskräfte; Familienpflege; Panel; EU-Staaten